The role of epigenetic modification in tumorigenesis and progression of pituitary adenomas: a systematic review of the literature. - Matthew Pease; Chao Ling; William J Mack; Kai Wang; Gabriel Zada (PLoS ONE)
Background Pituitary adenomas (PAs) are commonly occurring neoplasms with diverse endocrine and neurological effects. Although somatic gene mutations are uncommon in sporadic PAs, recent studies lend support to epigenetic modification as a potential cause of tumorigenesis and tumor progression. Methods A systematic literature review of the PubMed and Google Scholar databases was conducted to identify abstracts (n=1,082) pertaining to key targets and mechanisms implicated in epigenetic dysregulation of PAs published between 1993-2013. Data regarding histopathological subtype, target genes, mode of epigenetic modification, and clinical correlation were recorded and analyzed. Results Of the 47 that studies met inclusion criteria and focused on epigenomic assessment of PAs, only 2 were genome-scale analyses. Current evidence supports epigenetic alteration in at least 24 PA genes, which were categorized into four groups based on function and epigenetic alteration: 1) Sixteen tumor suppressor genes silenced via DNA methylation; 2) Two oncogenes overexpressed via histone acetylation and hypomethylation; 3) Three imprinted genes with selective allelic silencing; and 4) One epigenome writer inducing abnormal genome-scale activity and 5) Two transcription regulators indirectly modifying the genome. Of these, 5 genes (CDKN2A, GADD45y, FGFR2, caspase-8, and PTAG) showed particular susceptibility to epigenetic modification, with abnormal DNA methylation in >50% of PA samples. Several genes displayed correlations between epigenetic modification and clinically relevant parameters, including invasiveness (CDKN2A; DAPK; Rb1), sex (MAGE-A3), tumor size (GNAS1), and histopathological subtype (CDKN2A; MEG3; p27; RASSF1A; Rb1). Conclusions Epigenetic modification of selected PA genes may play a key role in tumorigenesis and progression, which may translate into important diagnostic and therapeutic applications.